PENERAPAN BAURAN PROMOSI TERHADAP PROMOSI PERPUSTAKAAN KEMENTERIAN KELAUTAN DAN PERIKANAN MELALUI MEDIA INSTAGRAM - Tsamrotul Fuadah; Anwar, Rully Khairul; Saefudin, Encang (Asosiasi Dosen Muda Indonesia, 2023)
Perpustakaan Kementerian Kelautan dan Perikanan need to carry out promotions to introduce themselves to their target users. The promotions of libraries through Instagram media is interesting to talk because it is one of the core activities that libraries carry out using media that is widely used by many people. This study uses a qualitative descriptive method to analyze and describe library promotion in detail with data collection techniques are observation, interviews, and literature studies. Data analysis techniques that used in this study are data reduction, data display, and conclusion drawing/verification. Perpustakaan Kementerian Kelautan dan Perikanan has implemented elements of the promotion mix are sales promotion by procuring quizzes with prizes and awarding the best library users, personal selling through giving responses in comments and Instagram DMs, public relations and publicity through holding public relations activities and publishing activities, and direct marketing through the dissemination of information directly through Instagram. Advertising is not carried out in library promotion. Keywords: promotions of libraries; promotio mix; Perpustakaan KKP